The Olympic Games, Sports Law and Human Rights - Mestre, Alexandre Miguel (Routledge Focus on Sport, Culture and Society Series, 2024)
This book explores the relationship between sports law, the Olympic Movement and human rights. Examining the historical legal roots of contemporary 'Olympic law', including the ancient history of the Olympic Games and the legacy of Pierre de Coubertin, the book shines new light on one of the most important issues in world sport today